Relationship between testosterone, oxidative stress biomarkers and antioxidant levels in male auto-mechanics in Ibadan, Nigeria (2016)
Hypogonadism attributable to males with metabolic syndrome was observed in automechanics occupationally exposed to mixed chemicals accompanied by oxidative stress (OS). We evaluated association between testosterone, OS biomarkers, enzymatic and non-enzymatic antioxidants in normal weight automechanics in Ibadan. This was a prospective cross sectional study involving 100 normal weight males aged 18 – 60 years. They were 50 automechanics in Ibadan, age and anthropometry matched with 50 eugonadic males from University College Hospital and environs (controls). Demographic, anthropometry, social habits and dietary history were obtained by standard methods. Blood (10mL) was collected and serum/plasma was used for biochemical analyses. Enzymatic antioxidants (catalase, glutathione peroxidase, superoxide dismutase (SOD) and glutathione -S- transferase (GST); non-enzymatic antioxidants (reduced glutathione (GSH), selenium and zinc), OS biomarkers (hydrogen peroxide (H2O2), malondialdehyde (MDA), total antioxidant capacity (TAC), total plasma peroxides (TPP) and oxidative Stress index (OSI) were estimated spectrophotometrically. Testosterone was assayed by enzyme immunoassay method (Dialab, Austria). Student’s t-test, Chi-square test and multiple regression were used for comparisons, associations and relationships respectively, which were significant at P<0.05. Testosterone, TPP, OSI, GST, MDA, H2O2, selenium and zinc concentrations were significantly higher while catalase and SOD concentrations were lower in automechanics than controls (P<0.05). However, testosterone levels in both groups were within the normal reference interval. TAC, OSI and GSH had significantly negative relationship while TPP had positive relationship with years at occupation in automechanics only (P<0.05). Automechanics may have OS but not hypogonadism probably due to increased antioxidant intake.